KAJIAN KESIAPAN SDM LOGISTIK MENGHADAPI ERA MEA - Fino Wahyudi Abdul; Cundo Harimurti; Resista Vikaliana (Jurnal Logistik Indonesia, 2017)
Asean Economic Community (AEC) implemented in 2015 is an effort to increase economic growth in Southeast Asia. Logistics is one of the priority integration sectors in the AEC.  In the logistics service sector, as a maritime country, Indonesia consists of thousands of islands which are inseparable unity. This condition makes Indonesia as a country that has import port transportation on front line and inter island transportation. In facing the , Indonesia is required to build an integrated National Logistics System (Sislognas).According to the Logistics Performance Index of World Bank 2010 Indonesia was ranked 75 out of 183 countries. Logistic system in Indonesia still need better handling, besides settling vision problem and mission which not yet integrated. In addition to infrastructure, vision and mission to support the improvement of business competitiveness in Indonesia is also not well integrated and coordinated. The system can be realized if supported by human resources who have logistics knowledge. Lack of human resources in the field of logistics more due to two factors, namely quality and speed.  With the implementation of AEC, the government and business people must be ready and face it by preparing business strategy, especially improving human resources in logistics so that Indonesia can compete in this era.Management professionalism, information systems, culture, functional strategies must run simultaneously to achieve a corporate objective. In facing the challenges of globalization of companies or businesses, government and academia need to develop national workforce such as improving the quality of curriculum, as well as effective training to support and improve the quality and motivation of human resources.